2022
DOI: 10.1111/1365-2664.14193
|View full text |Cite
|
Sign up to set email alerts
|

Abandoned pastures and restored savannas have distinct patterns of plant–soil feedback and nutrient cycling compared with native Brazilian savannas

Abstract: 1. Around 40% of the original Brazilian savanna territory is occupied by pastures dominated by fast-growing exotic C 4 grasses, which impact ecosystem nutrient cycling. The restoration of these areas depends on the re-establishment of soil processes.2. We assessed how restoration of abandoned pastures through direct seeding of native species and land-management practices (burning and ploughing) affect soil nutrient cycling dynamics compared with native savannas. We compared the activity of soil enzymes related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Soil enzymes can participate in nutrient cycling and transformation extensively and are key properties to reflect soil fertility [ 38 ]. This study indicated that compared with clean tillage, sod culture enhanced the activity of soil urease, catalase, sucrase, and phosphatase significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Soil enzymes can participate in nutrient cycling and transformation extensively and are key properties to reflect soil fertility [ 38 ]. This study indicated that compared with clean tillage, sod culture enhanced the activity of soil urease, catalase, sucrase, and phosphatase significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the soil seed bank being considered transient and species‐poor in Cerrado (Buisson et al, 2019), we demonstrated that it could bring back key target species. It can also inoculate endemic microorganisms that can help native species to establish in degraded sites (D'Angioli et al, 2022; Martins et al, 1999). Furthermore, the transplant technique could bring subshrubs diversity, approximating the growth forms proportionality to that of reference ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Andropogon fastigiatus has been widely sown in large‐scale projects aiming to restore Cerrado grassland in the region because its rapid growth covers the soil rapidly (Pellizzaro et al., 2017), theoretically limiting the space for exotics. Recent studies have shown that after a few years, these restored areas have a high proportion of fast‐growing and short‐lived species (Giles et al., 2022), which in turn maintain higher nutrient cycling in comparison to conserved native areas (D'Angioli et al., 2022). Compositional changes in these areas showed increasing exotic species coverage and dominance (Coutinho et al., 2019).…”
Section: Discussionmentioning
confidence: 99%